Evaluation of the Utilization of the Civil Service Information System (SIASN) Application for Name and NIP Correction Services - Naibaho, Kanro Johannes; Supriyatno, Budi; Hakim, Azis (Dinasti Publisher, 2025)
Efficient and accessible civil service is an important aspect of a country's development. Indonesia, as a country with a large and diverse civil service and a vast territory, faces complex challenges in providing equitable access to civil service for all civil servants. However, with rapid advances in information and communication technology, electronic-based government systems have emerged as a potential solution to improve service accessibility in Indonesia. The purpose of this study is to evaluate electronic-based government systems in improving the accessibility of public services in Indonesia and the benefits generated for the civil service (ASN). The Civil Service Information System (SIASN) is a digital platform developed by the State Civil Service Agency to manage ASN data and information in Indonesia. This study aims to evaluate the SIASN-based name and NIP correction service policy based on State Civil Service Agency Regulation Number 7 of 2023. This study uses a descriptive analytical approach by collecting data through literature studies and analysis of related documents. The results show that electronic-based government systems play an important role in improving the accessibility of public services and civil service in Indonesia. By reducing physical barriers, increasing efficiency, and providing additional benefits such as transparency and more active public participation, these systems can accelerate public service processes and increase the satisfaction of the civil service. To optimize the role of the electronic-based government system, joint efforts are needed between the civil service (ASN) and personnel managers in improving infrastructure, digital literacy, and data protection in order to accelerate personnel services in terms of correcting the names and NIP of civil servants (ASN) through the SKK SIASN application of the Civil Service National.